2010
DOI: 10.1210/me.2010-0179
|View full text |Cite
|
Sign up to set email alerts
|

Research Resource: Estrogen-Driven Prolactin-Mediated Gene-Expression Networks in Hormone-Induced Prostatic Intraepithelial Neoplasia

Abstract: Cotreatment with testosterone (T) and 17β-estradiol (E2) is an established regimen for inducing of prostatic intraepithelial neoplasia (PIN) and prostate cancer in rodent models. We previously used the pure antiestrogen ICI 182,780 (ICI) and bromocriptine, a dopamine receptor agonist, to inhibit PIN induction and systemic hyperprolactinemia in Noble rats and found that the carcinogenic action of T+E2 is mediated directly by the effects of E2 on the prostate and/or indirectly via E2-induced hyperprolactinemia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In one recent study, 2504 genes were identified as having their expression significantly altered in rat lateral prostate by treatment with testosterone and estradiol. Of these, 80% were blocked by cotreatment with the antiestrogen ICI and bromocriptine, which blocks production of prolactin in the pituitary gland [106]. However, only 10% of these changes could be blocked by ICI alone, suggesting that not only does prolactin play an important role in mediating these changes, but also that centrally produced, rather than local, prolactin is involved.…”
Section: Hyperprolactinemiamentioning
confidence: 99%
“…In one recent study, 2504 genes were identified as having their expression significantly altered in rat lateral prostate by treatment with testosterone and estradiol. Of these, 80% were blocked by cotreatment with the antiestrogen ICI and bromocriptine, which blocks production of prolactin in the pituitary gland [106]. However, only 10% of these changes could be blocked by ICI alone, suggesting that not only does prolactin play an important role in mediating these changes, but also that centrally produced, rather than local, prolactin is involved.…”
Section: Hyperprolactinemiamentioning
confidence: 99%
“…In an estrogen-induced PCa model [14][17], fulvestrant prevented the evolution of precancerous lesions, reversed the E2-induced transcriptome [16], [17], and induced its own gene signature [16]. In DU145, a human PCa cell line that expresses ERβ and no ERα, fulvestrant suppressed cell growth via the receptor [18] and regulated a unique set of genes, possibly through cross-talk between ERβ and NFκB [19].…”
Section: Introductionmentioning
confidence: 99%
“…Prolactin has been shown to be involved in the differentiation and proliferation of numerous tissues, including the prostate gland (Crepin et al, 2007). And estrogen appears to be induced hyperprolactinemia as an important mediator of estrogen action in prostate carcinogenesis (Tam et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of estrogen on prostate tissue were documented by many authors (Risbridger et (Tam et al, 2010). The objective of this study was to investigate the changes in glucose, total protein, albumin, calcium concentrations as a result of injection of estradiol benzoate (EB) in male rabbits.…”
Section: Introductionmentioning
confidence: 99%